Pengaruh Media Sosial Terhadap Hubungan Sosial di Era Digital - Fasikul Ikhsan; Fahiratun Afiat Muizunzila; Nur Riswandy Marsuki (Lembaga Pengembangan Kinerja Dosen, 2024)
Social media has a very important role in social relations in the digital era like today. Social media in social relations refers to the use of social media platforms to interact and communicate with other people. Social media allows individuals to interact with people from various backgrounds and expand their social networks. Apart from that, social media can also influence individuals' behavior and communication patterns in their social relationships. The use of social media can have positive impacts such as facilitating interaction and expanding relationships, but it can also have negative impacts such as spreading misinformation and decreasing privacy. The positive and negative impacts of social media must be taken into account. This research aims to analyze the influence of social media on social relationships in the digital era. The research method uses qualitative methods with a literature study type of research. The research results: 1) Increased interaction and use of social media, 2) Changes in communication patterns, 3) Positive and negative impacts of Social Media. Social media has a significant influence on social relationships in the digital era. As a researcher or user of social media, it is important to understand its impact and use it wisely